2020
DOI: 10.1186/s12870-020-02380-w
|View full text |Cite
|
Sign up to set email alerts
|

Wide crossing diversify mitogenomes of rice

Abstract: Background: In most angiosperms, the inheritance of the mitochondria takes place in a typical maternal manner. However, very less information is available about if the existence of structural variations or not in mitochondrial genomes (mitogenomes) between maternal parents and their progenies. Results:In order to find the answer, a stable rice backcross inbred line (BIL) population was derived from the crosses of Oryza glaberrima/Oryza sativa//Oryza sativa. The current study presents a comparative analysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 65 publications
0
10
0
Order By: Relevance
“…Sugarcane, for example, has two circular contigs as the complete mitogenome [ 68 ]. As we find in A. longiglumis , rearrangements involving inversion, translocation, fusion, and fission have also been shown in mitochondrial genomes of rice, with various frequencies of alternatives [ 69 ]. For most cultivated grasses, the complex and polyploid large nuclear genome, and low copy number of mitochondria, pose a challenge to the amount of data being able to be sequenced [ 19 , 21 ].…”
Section: Discussionmentioning
confidence: 70%
“…Sugarcane, for example, has two circular contigs as the complete mitogenome [ 68 ]. As we find in A. longiglumis , rearrangements involving inversion, translocation, fusion, and fission have also been shown in mitochondrial genomes of rice, with various frequencies of alternatives [ 69 ]. For most cultivated grasses, the complex and polyploid large nuclear genome, and low copy number of mitochondria, pose a challenge to the amount of data being able to be sequenced [ 19 , 21 ].…”
Section: Discussionmentioning
confidence: 70%
“…sativa, and the maternal parent line O. glaberrima, were used in the paper. The planting and management of the rice lines followed the methods in our previous study [23].…”
Section: Plant Materialsmentioning
confidence: 99%
“…Repeats may control the expression of the gene in both plastids [36] and mitochondria [37], which has been reported in previous studies. In BIL mitogenomes, the gene expression was influenced by repeat recombination [23]; therefore, we wondered if the same thing happened in plastomes. Our analysis showed that fewer repeats were found in plastomes compared to mitogenomes; however, almost all repeats were distributed in the regions located 2 Kb upstream or downstream from genes (Supplementary Table S3).…”
Section: Expressional Profile Of Plastid Genes In Bilsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cotton A, D and AD mt genomes differed drastically and had four or six large repeats leading to lot of inversions and translocations. Mt genomes of rice wide crosses and backcross inbred lines have shown radical change in the gene order and copy number (Yang et al 2020). In Fabales, a different kind of genome expansion has occurred in mt genomes.…”
Section: Introductionmentioning
confidence: 99%